2013
DOI: 10.13005/bpj/376
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infections among Pregnant Women in Makkah, Saudi Arabia

Abstract: Urinary tract infection (UTI) is one of the most common infections where one or more part of urinary system become infected usually after bacteria overcome the natural defence mechanism of urinary tract (Al-Dujiaily, 2000). Although UTI could affect both sexes, women are more frequently affected than men due to short urethra, loss of prostatic secretion, ease of urinary tract contamination by faecal flora and various other reasons. In women however, the incidence of UTI is more frequent in pregnant women as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
5
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 17 publications
3
24
5
5
Order By: Relevance
“…The results revealed that 20% of the pregnant women were positive for UTI with symptomatic UTI cases more than asymptomatic ones. [8] So this prevalence was also higher than our study. Also, the number of symptomatic UTI in our study (93.5%) is more than asymptomatic cases (6.5%) which is a similar finding to this study.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…The results revealed that 20% of the pregnant women were positive for UTI with symptomatic UTI cases more than asymptomatic ones. [8] So this prevalence was also higher than our study. Also, the number of symptomatic UTI in our study (93.5%) is more than asymptomatic cases (6.5%) which is a similar finding to this study.…”
Section: Discussioncontrasting
confidence: 63%
“…This is much lower than that of Makkah, KSA (20 %). [8] However, a tertiary center in Jeddah, has reported UTI prevalence as low as 1.7%. [9] In a study conducted at the antenatal clinic of Abha General Hospital, KSA, during September 2012 to January 2013, 12.7% of 402 pregnant women were affected with UTI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, early screening and health education of pregnant women about the preventive measures of UGIs is strongly advocated. Antenatal care should include direct questioning and urine examination to discover asymptomatic cases [9,10].…”
Section: Introductionmentioning
confidence: 99%